Engineering modular and tunable genetic amplifiers for scaling transcriptional signals in cascaded gene networks. Issue 14 (16th July 2014) - Wang, Baojun; Barahona, Mauricio; Buck, Martin
Abstract: Synthetic biology aims to control and reprogram signal processing pathways within living cells so as to realize repurposed, beneficial applications. Here we report the design and construction of a set of modular and gain-tunable genetic amplifiers in Escherichia coli capable of amplifying a transcriptional signal with wide tunable-gain control in cascaded gene networks. The devices are engineered using orthogonal genetic components ( hrpRS, hrpV and P hrpL ) from the hrp (hypersensitive response and pathogenicity) gene regulatory network in Pseudomonas syringae . The amplifiers can linearly scale up to 21-fold the transcriptional input with a large output dynamic range, yet not introducing significant time delay or significant noise during signal amplification. The set of genetic amplifiers achieves different gains and input dynamic ranges by varying the expression levels of the underlying ligand-free activator proteins in the device. As their electronic counterparts, these engineered transcriptional amplifiers can act as fundamental building blocks in the design of biological systems by predictably and dynamically modulating transcriptional signal flows to implement advanced intra- and extra-cellular control functions.